Twenty four hour variation in plasma atrial natriuretic factor during VVI and DDD pacing. Issue 6 (June 1996) - Vardas, P. E.; Markianos, M.; Skalidis, E.; Simantirakis, E.; Manios, E.; Papavasiliou, E.
Abstract : OBJECTIVE: To investigate whether plasma atrial natriuretic factor (ANF) follows a pattern of circadian variation similar to that of other hormones in patients paced under VVI and DDD pacing modes and to determine if the known effect of pacing mode on ANF secretion is maintained throughout the 24 hour period. PATIENTS AND DESIGN: 20 patients were studied. They had complete atrioventricular block and had been paced for 17 (SD 3.5) months with a dual chamber multiprogrammable pacemaker. They were divided into two groups according to the duration of pacing in either VVI or DDD mode before the measurements: group A, n = 11 (8 men, 3 women, aged 65 (7) years), each paced for 24 h under each of VVI and DDD modes in random order; group B, n = 9 (7 men, 2 women, aged 63 (8) years), each paced for 60 d under each pacing mode before the measurements. Blood samples were taken and ANF concentrations measured every 4 h over a 24 h period, starting at 09.00. Measurements were also made of plasma cortisol, which has a known circadian pattern, so that the 24 h curve could be compared with that of ANF. RESULTS: In contrast to cortisol, ANF values indicated a pulsatile pattern of secretion throughout the 24 h period, with no clear circadian variation. In group B, ANF concentrations were significantly higher during VVI than during DDD pacing throughout the 24 h period, whereas in group A this difference was statistically significant only at certain times of day. CONCLUSIONS: ANF does not show the circadian pattern of variation shown by cortisol and other hormones. Dual chamber pacing contributes to an improvement not only in cardiac haemodynamics but also in the neuroendocrine system, especially in the long term.